Myocardial mechanics in dilated cardiomyopathy: prognostic value of left ventricular torsion and strain - Ochs, Andreas; Riffel, Johannes; Ochs, Marco; Arenja, Nisha; Fritz, Thomas; Galuschky, Christian; Schuster, Andreas; Bruder, Oliver; Mahrholdt, Heiko; Giannitsis, Evangelos; Frey, Norbert; Katus, Hugo; et al. (Journal of cardiovascular magnetic resonance, 2021)
Data on the prognostic value of left ventricular (LV) morphological and functional parameters including LV rotation in patients with dilated cardiomyopathy (DCM) using cardiovascular magnetic resonance (CMR) are currently scarce. In this study, we assessed the prognostic value of global longitudinal strain (GLS), global circumferential strain (GCS), global radial strain (GRS) and LV torsion using CMR feature tracking (FT).
Gesehen am 20.01.2022